2018
DOI: 10.1007/s10646-018-1974-9
|View full text |Cite
|
Sign up to set email alerts
|

Response of Zea mays to multimetal contaminated soils: a multibiomarker approach

Abstract: Heavy metals present in mine tailings pollute agroecosystems, put the integrity of the environment at risk and become a major route of exposure to humans. The present study was carried out in Taxco, Guerrero, Mexico, where millions of tons of mine tailings have been deposited. Soils from this region are used for agricultural activities. Maize (Zea mays) was selected as a test plant, because it is one of the most common and important cereal crops in Mexico and worldwide. Thirteen metals were selected and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…Wei et al (2020) found that most of the metals, such as Pb, Zn, Cr, and Mn, were mainly accumulated in the roots. Results show that in general, individuals exposed to multimetal contaminated soils were smaller, had altered leaf shape structures, and altered micromorphological characters (Ruiz-Huerta et al 2017;Tovar-Sánchez et al 2018;Kabata-Pendias 2000). All these data are consistent with the results obtained in this study.…”
Section: Plant Growth and Developmentsupporting
confidence: 90%
See 2 more Smart Citations
“…Wei et al (2020) found that most of the metals, such as Pb, Zn, Cr, and Mn, were mainly accumulated in the roots. Results show that in general, individuals exposed to multimetal contaminated soils were smaller, had altered leaf shape structures, and altered micromorphological characters (Ruiz-Huerta et al 2017;Tovar-Sánchez et al 2018;Kabata-Pendias 2000). All these data are consistent with the results obtained in this study.…”
Section: Plant Growth and Developmentsupporting
confidence: 90%
“…Metal accumulation varies depending on the plant developmental stage as shown for 30 and 70 day maize plants (Ruiz and Armienta 2012). It is known that heavy metals affect signi cantly plant growth in maize, including roots, leaves, cobs, and stems (Wei et al 2020;Anjhum et al 2016;Tovar et al 2018). Additionally, Ruiz and Armienta, (2012) and Drlickova et al (2013) found that As is also harmful for maize growth.…”
Section: Plant Growth and Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of such tools is currently increasing in the field of biomonitoring and bioremediation. Some biomarkers that have already been reported in plants are the following: oxidative stress by the production of reactive oxygen species [95], the reduction of macromorphological parameters such as plant height, stem diameter, and the number of leaves and negative modifications in chloroplasts with implications in photosynthesis [96]. These have been useful biomarkers for showing the adverse effects of metal exposition on the development, growth, and physiology of different plants exposed to this type of stress [97,98].…”
Section: Correlation Between Physiological and Biochemical Parameters...mentioning
confidence: 99%
“…Indeed, visible symptoms of heavy metal toxicity include chlorosis, leaf rolling and necrosis, senescence, wilting and stunted growth, low biomass production, limited numbers of seeds, and eventually death [58]. For example, reduction in morphological attributes of height, coverage, or biomass derived from exposure to HM has been reported in Arundo donax (Poaceae), exposed to As, Cd, and Pb [59]; Zea mays (Graminaceae) exposed to Cd, Fe, Ni, and Zn [60]; Prosopis laevigata (Fabaceae [61]), Pithecellobium dulce (Fabaceae [22]), Vachellia farnesiana (Fabaceae [21]), and Wigandia urens [23] exposed to Cu, Pb, and Zn.…”
Section: Plants As Biosensorsmentioning
confidence: 99%